Lost in a plethora of concerns? Match, mismatch and hypnotism: The case of the New Zealand public sector - Chatterjee, Bikram; Mirshekary, S. (University of Wollongong, 2007)
The paper is centred on the theme that the significance attached to attaining higher ‘efficiency’ standards in monetary/ numeric terms to attain better ‘economy’ in New Zealand may have led to a change in concept of ‘ethics.’ This is due to higher stress attached during the New Zealand public sector reform to attaining higher efficiency and economic supremacy compared to before the reform. Again, an endeavour to attain economic supremacy at the macro level does not lead to attaining higher efficiency standards at the specific organisational levels and vice versa. The authors suggest that the hypnotic state of the authors has been brought by a dearth of research in regard to the match/mismatch of these three Es, that is, economy, efficiency and ethics. Following this hypnotic state of authors’ future research is suggested in regard to the conceptual schema of existence of these three Es in New Zealand public sector.